Strategi Pembelajaran Inovatif untuk Peningkatan Mutu Pendidikan: (Suatu Tinjauan Konseptual dengan Pendekatan Teknologi Pendidikan) - A. Abdullah (Jurnal Profesi Kependidikan, 2012)
Education, that is conducted in order to fulfill the demand of the 1945 Constitution to educate the nation, is a very complex process. Internationally, we are still unable to compete and lag behind education-wise. Nevertheless, government of Indonesia has always given their utmost attention to the quality of education by finding new approach to teaching and learning. A variety approach such as Development Program of Instructional System (PPSI), Student Active Learning (CBSA), Competency Based Curriculum (KBK), and Level of Education Curriculum (KTSP) were applied once in a time to find instructional strategy that suit to the demand of the era. Unfortunately, we have yet to improve the quality of instruction that we dream about. This paper presents an innovative instructional strategy that focuses on instructional vision, systematical approach, and valid and reliable measurement in order to facilitate students to fulfill the required goals. Furthermore, this paper also discusses the need of visionary educational strategy that is able to help students to create their future dream. At the end, the paper presents the important of the user, the school, and the students, or otherwise known as the safety triangle that represents stakeholders, in setting the level of education relevance. Key words: quality of education, innovative instructional strategy, safety triangle